ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PIUTANG TAK TERTAGIH PADA PT.KAWASAN INDUSTRI MEDAN (PERSERO) DENGAN MOTIVASI MEMBAYAR SEBAGAI VARIABEL MODERATING - Endang Budiwati Sinaga (Jurnal Ekonomi dan Bisnis (EK&BI), 2019)
The objective of this study was to analyze the influence of costumer satisfation, collectability, the stability of costumer sales, the pay motivation as moderating variable of doubtful account receivable of PT.KAWASAN INDUSTRI MEDAN(Persero). The study used causal research method.The population in the study is the tenants that located in Kawasan Industri Medan (Medan Industrial Park) and all of them were used as the samples (Proportionate stratified random sampling). Primary data were gathered by using questionares.Hypothesis was tested by using multiple regression analysis and residual test with an SPSS software program. The result of the study showed that costumer satisfation, collectibility,and the stability of costumer sales had significant influence on doubtful account receivable simultaneously. Partially, costumer satisfation, and the stability of costumer sales had positif significant influence on doubtful account receivable. Pay Motivation as moderating variable could moderate the correlation of costumer satisfaction, collectability, stability of costumer sales with doubtful account receivable on PT.KAWASAN INDUSTRI MEDAN (Persero). The objective of this study was to analyze the influence of costumer satisfation, collectability, the stability of costumer sales, the pay motivation as moderating variable of doubtful account receivable of PT.KAWASAN INDUSTRI MEDAN(Persero). The study used causal research method.The population in the study is the tenants that located in Kawasan Industri Medan (Medan Industrial Park) and all of them were used as the samples (Proportionate stratified random sampling). Primary data were gathered by using questionares.Hypothesis was tested by using multiple regression analysis and residual test with an SPSS software program. The result of the study showed that costumer satisfation, collectibility,and the stability of costumer sales had significant influence on doubtful account receivable simultaneously. Partially, costumer satisfation, and the stability of costumer sales had positif significant influence on doubtful account receivable. Pay Motivation as moderating variable could moderate the correlation of costumer satisfaction, collectability, stability of costumer sales with doubtful account receivable on PT.KAWASAN INDUSTRI MEDAN (Persero).